Molecular characterization and safety assessment of biofortified provitamin A rice - Oliva, Norman; Florida Cueto-Reaño, Maria; Trijatmiko, Kurniawan R.; Samia, Mercy; Welsch, Ralf; Schaub, Patrick; Beyer, Peter; Mackenzie, Donald; Boncodin, Raul; Reinke, Russell; Slamet-Loedin, Inez; Swamy, B.P. Mallikarjuna (Springer, 2020)
Part of the studies involved in safety assessment of genetically engineered crops includes characterizing the organization, integrity, and stability of the inserted DNA and evaluating the potential allergenicity and toxicity of newly-expressed proteins. Molecular characterization of the introduced DNA in provitamin A biofortified rice event GR2E confirmed insertion of a single copy of the transfer-DNA in the genome and its inheritance as a single locus. Nucleotide sequencing of the inserted DNA confirmed it was introduced without modifications. The phytoene synthase, and carotene desaturase proteins did not display sequence similarity with allergens or toxins. Both proteins were rapidly digested in simulated gastric fluid and their enzymatic activity was inhibited upon heat treatment. Acute oral toxicity testing of the protein in mice demonstrated lack of adverse effects. These evidences substantiated the lack of any identifiable hazards for both proteins and in combination with other existing comparative analyses provided assurance that food derived from this rice is safe. This conclusion is in line with those of the regulatory agencies of US Food and Drug Administration, Health Canada and Food Standard Australia and New Zealand.